SRGAP2 and the gradual evolution of the modern human language faculty. Issue 1 (11th January 2018) - Martins, Pedro Tiago; Marí, Maties; Boeckx, Cedric
Abstract: In this article, we examine a new source of evidence that draws on data from archaic human genomes to support the hypothesis that vocal learning in Homo preceded the emergence of anatomically modern humans. We build our claim on the evolutionary history of the SLIT-ROBO GTPase 2 gene ( SRGAP2 ). The SLIT-ROBO molecular pathway has been shown to have an important role in the context of vocal learning. Though the relevance of the SRGAP2 gene duplication in the emergence of some aspect of language has not gone completely unnoticed, recent results now allow us to articulate a mechanistic hypothesis of its role in the context of axon guidance. Specifically, SRGAP2C, a duplication of SRGAP2 crucially also found in Neanderthals and Denisovans, but not in extant mammals, inhibits the ancestral SRGAP2A, which in turn modulates the axon guidance function of the SLIT-ROBO molecular pathway. This, we claim, could have contributed to the establishment of the critical cortico-laryngeal connection of the vocal learning circuit. Our conclusions support the idea that complex vocal learning could already have been part of the arsenal of some of our extinct ancestors.